Chamberlin Versus Chicago - Archibald, G. C. (Review of Economic Studies, 1961)
Journal Article Chamberlin versus Chicago Get access G. C. Archibald G. C. Archibald London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 1, October 1961, Pages 2–28, https://doi.org/10.2307/2296178 Published: 01 October 1961